Demographic challenges and agricultural abandonment: Solutions for semi-arid winegrowing regions - Calafat Marzal, Consuelo (2023)
• Demographic dynamics influence vineyard abandonment in semi-arid areas. • High abandonment pathways include the absence of a protected designation of origin. • Subsidies or sector measures mitigate abandonment in depopulated areas. • Demographic dynamics affect the strategy towards productivism or multifunctionality. • Abandonment in non-depopulated areas is mitigated with multifunctional land plots.